Manufactured Yttrium Barium Copper Nano Oxide for Medicinal Applications - Rania Daha; Manel Bouloudenine; Katia Djenadi; Tarek Tahraoui; Stefano Bellucci; Abdelaziz Rabehi (The Journal of Engineering and Exact Sciences)
In light of the considerable interest surrounding the antibacterial properties of nanometal oxides and high-temperature superconductors, this study focuses on the synthesis of YBa2Cu3O7 (YBCO) using the Sol-Gel method. The research delves into the experimental aspects of nanoparticle (NP) synthesis and aims to elucidate the antibacterial potential of YBCO NPs, a high-temperature superconductor, against four distinct bacteria. These bacteria were subjected to varying concentrations of YBCO NPs (0.01 mg/ml, 0.025 mg/ml, 0.05 mg/ml, and 0.1 mg/ml). Comprehensive characterization of the synthesized nanoparticles encompassed techniques such as X-ray diffraction (XRD), scanning electron microscopy (SEM), differential scanning calorimetry (DSC), and thermogravimetric (TG) analysis. Remarkably, the Gram-positive strains, including Staphylococcus epidermidis and Methicillin-resistant Staphylococcus aureus (MRSA), exhibited pronounced susceptibility to the YBCO NPs, while Gram-negative strains displayed minimal response. Intriguingly, even at elevated concentrations of 0.01, 0.025, 0.05, and 0.1 mg/ml, these bacterial strains showcased resilient resistance. This research sheds light on the potential of YBCO NPs as an antibacterial agent against specific pathogens.